Lean impact on manufacturing productivity: a case study of industrialized building system (IBS) manufacturing factory - Zainal Abidin, Muhammad Harith; Leman, Zulkiflle; Mohd Yusof, Zainal Abidin; Khalili, Amjad (Penerbit Universiti Teknologi Malaysia, 2022)
According to a recent study, Lean Manufacturing (LM) adoption in the Malaysian Industrialized Building System (IBS) industry is still low due to a variety of barriers, including misconceptions, the use of modular coordination, a lack of detailed guidelines and the Lean culture is still in its infancy in the field of IBS. This paper examines the impact of Lean Manufacturing approaches towards the manufacturing productivity in Malaysian IBS Manufacturing factory. An integration method of Value Stream Mapping (VSM) and benchmarking for measuring manufacturing plant performance and total productivity is offered. The company was able to improve its performance in each manufacturing department by implementing a lean approach. After improvement, the overall manufacturing plant performance index increased from 0.75 to 0.78, resulting in a 4.00 percent increase in total factor productivity. The proposed improvement features extracted from essential lean methods such as JIT, TPM and CI can be used by practitioners to increase the level of Lean Manufacturing implementation in Malaysian manufacturing firms.